Effects of salinity on ZOANTHUS SOCIATUS (Cnidaria: Anthozoa): Is low salinity a limiting factor? - Soares, Macelo de Oliveira; Sousa, Leonardo Peres de (My University, 2011)
Abiotic factors, such as variations on salinity, exert influence on the animal distribution in the intertidal zone, including zoanthids. This study evaluated the osmotic, morphological and ethological effects of salinity variations on tropical zoanthid Zoanthus sociatus. In order to analyze the hypothesis of osmotic conformation, the zoanthid was submitted to salinity stress. To estimate the osmotic capabilities of the species studied, specimens collected in beach rocks were taken alive to the laboratory and maintained in water collected from the site. The osmoregulatory ability of Z. sociatus was determined by measuring the hemolymph osmolality under various salinity conditions and comparing it to the medium osmolality. Zoanthid Z. sociatus is able to present osmotic conformation in hemolymph salinity in a wide range of external salinity values. The bleaching frequency was high in low salinities and the mortality rate was high after two days of experiment. This experiment shows for the first time the importance of osmotic conformation in a tropical zoanthid and discusses the role of low salinity as a limiting factor for survival and distribution of these important animals in tropical coastal reefs.